Analisis Kebutuhan Siswa dalam Pembelajaran Tata Bahasa Inggris: Konteks ESP - Sri Rejeki (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study investigates students' needs for grammar learning in English class in English for Specific Purposes (ESP) context. This study uses a quantitative research methodology with a survey design. Data were collected from ESP students at an English language institution, specifically taking classes for police registration. The findings show that students already have reasonable goals in learning grammar, and almost all students also agree with the necessity of learning grammar. Even so, students still have difficulties in learning grammar and implementing it. Thus, a better method is needed in teaching grammar according to the needs and interests of students. Therefore, students can understand grammar learning in all English skills. It is recommended that future researchers dig deeper into the strategies that can be used so that grammar learning becomes more effective according to students' needs.